Physics Terms Created Using the Kalkalaw Method (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
The terminology of the Karakalpak language has developed its own historical path. Over the years, various terms have been incorporated into our terminology from different sources. Many of them have been adapted from other languages, both through direct borrowing and through translation.